STRATEGI PENGEMBANGAN INDUSTRI KECIL LANTING DIKABUPATEN KEBUMEN - Puspitasari, Atika Tri; Widiyanto, Widiyanto (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
The purpose of this research was to describe and analyze the strategy of production, marketing, human resources (labor) and capital. The technique of collecting data through observation, interviews, documentation, questionnaires and triangulation. The technique of sampling was done deliberately (purposive sampling). The results of this research showed that the strategy of production by means of the best raw materials came from the area of Kebumen through raw material suppliers, the addition of flour to address scarce raw materials, traditional means of production and use of appropriate technology, production place are located near the house of the manufacturer, the use of the workforce that has the skills, packaging innovation products and adding product type. Marketing strategies by way of increased order coupled with the trademark shows as well as various flavors of innovation development, adjustment of the selling price with the price of raw materials production, the cooperation of manufacturers and suppliers in the distribution of lanting, promotional activities by means of cooperation with the agency and related service trade off products online. The strategy of human resources with the formation groups of industry in the village of lemahduwur (but not running smoothly), follow and avail the opportunity of education and training from the government, division of labor, the addition of a number of labor, granting additional wages for labor remains. Strategy capitalÂ with the initial capital came from his capitalÂ own and profit as capital accumulation, additional capital when many party and by feast day; increased access to capital, financial administration and against accounting in a simple and routine. The advice given is the government and manufacturers improve HR, technology development, marketing and capital. Manufacturer improves collaboration with suppliers of raw materials, maintaining the typical features and making a trademark.The Government and manufacturers more cooperation and mutual exchange of information more closely and thoroughly in education and training.